Levantamiento de procesos de la unidad académica de ciencias de la ingeniería y aplicadas como parte del sistema de gestión de la Universidad Técnica de Cotopaxi - Tipán Defaz, Rosa Elvira (2016)
This research arises from the need to define the processes for Academic Unit of Science and Applied Engineering as part of management system at Cotopaxi Technical University in order to improve the job performance and thus achieve academic - Administrative excellence by incorporating the EFQM Model (European Foundation for Quality Management), based on an approach process. The EFQM Model is a flexible and adaptable system with other standards, models and tools that covers all aspects, areas and the organization levels as it represents a framework for the management of any organization. Once the analysis of process completed through the nine criteria of the EFQM Model respective Process and Procedures Manual is made….